Elevated HbA1c is not a risk factor for wound complications following total joint arthroplasty: a prospective study. (September 2020) - Citak, Mustafa; Toussaint, Bastian; Abdelaziz, Hussein; Klebig, Felix; Dobinsky, Alexandra; Gebauer, Matthias; Gehrke, Thorsten
Background: Controversies exist regarding the association of elevated serum glycated haemoglobin (HbA1c) levels and postoperative surgical site infection (SSI) or prosthetic joint infection (PJI) in the setting of total hip and knee arthroplasty (THA and TKA). The purpose of the current study was to determine the prevalence of unknown and uncontrolled diabetes mellitus (DM) in a consecutive series and to investigate the association between postoperative wound complications or SSI/PJI and elevated HbA1c in patients undergoing TJA. Methods: In this prospective single-centre study, HbA1c was determined for patients undergoing elective primary, aseptic or septic revision THA and TKA, between September 2017 and March 2018. Prevalence of DM, unknown and uncontrolled diabetes were reported. Occurrence of 90-day wound healing disorders (WHD) as well as SSI or PJI were observed. Considering the HbA1c threshold ⩾6.5%, a comparative analysis between patients with and without WHD and SSI or PJI for the whole study cohort, as well as for each arthroplasty group, was performed. Receiver operating characteristic (ROC) curves were developed to quantify the predictive power of HbA1c with regard to WHD and infection complications. A total of 1488 patients were included for final analysis. There were 1127 primary THA and TKA (75.7%), 272 aseptic revisions (18.3%) and 89 septic revisions (6.0%). The known diabetic patients constituted 9.9% of the whole study cohort. Results: The majority had uncontrolled DM (67%). Prevalence of unknown DM was 11.1%. The results reveal the prevalence for the German population and might be different in other regions. A total of 57 patients (3.7%) experienced postoperative wound or infectious complications. PJI occurred in only 5 patients (0.03%). There was no significant difference between patients with HbA1c <6.5% and patients with HbA1c ⩾6.5% ( p = 0.092). Conclusions: We demonstrated that prevalence of unknown and uncontrolled DM in patients undergoing TJA is increasing, however; routine preoperative determination of the HbA1c value to prevent possible postoperative wound or infectious complications remains debatable. Larger studies investigating the optimal HbA1c level, as well as other predictors are required.